SYSTEMATICS AND PHYLOGENY OF THE GENUS AMEGHINOMYA IHERING, 1907 (BIVALVIA: CHIONINAE) FROM THE CENOZOIC OF ARGENTINA AND CHILE (Ameghiniana, 2013)
A systematic revision of the genus Ameghinomya Ihering, 1907 is conducted and its phylogenetic relationships are explored through a cladistic analysis based on morphological characters of extant and fossil species. The resulting strict consensus shows one clade consisting of Protothaca Dall and Austrovenus Finlay and another one encompassing the species of Ameghinomya, the latter being monophyletic. Ornamentation of the valves is shown to have systematic value which until now had not been appropriately explored. Based on the results of the phylogenetic and systematic analysis, it is proposed to assign the species Venus antiqua King, 1832 (extant, Southwestern Atlantic) and Venus chiloensis Philippi, 1887 (Miocene, Chile) to the genus Ameghinomya. Ameghinomya camachoi sp. nov. is described from the Carmen Silva Formation (Miocene, Isla Grande de Tierra del Fuego, Argentina)